Perancangan Mesin Pencacah Polimer Komposit Kapasitas 10 kg/Jam - Pangaribuan, Rhenaldy Primananda; Iswandi, Iswandi (CV. IRA PUBLISHING, 2025)
The increasing volume of composite plastic waste poses serious challenges to the environment, so practical and sustainable treatment solutions are needed. This research aims to design a composite plastic shredding machine with a capacity of 10 kg/h, suitable for small industries and households. The design method employed a quantitative approach, incorporating frame analysis, a V-belt transmission system, and the selection of a carbon steel blade. The results show that the machine can achieve the target capacity with low energy consumption and good structural stability. The study's conclusion confirms that this machine has the potential to be an effective solution in supporting sustainable plastic recycling programs on a local scale.